Kampanye Lingkungan Hidup Forum Komunitas Hijau dalam Pelestarian Alam di Kota Banjarmasin - Lalita Hanief; Noviana Sari; Andika Sanjaya (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2019)
Waste management and greening are noteworthy problems in Banjarmasin rivercity. The purpose of this study was to determine the implementation of “ForumKomunitas Hijau” (FKH) Environmental Campaign in Nature Conservation inBanjarmasin City. This research uses a descriptive qualitative approach. Data collectiontechniques using semi-structured interviews, documentation, library research, with dataanalysis techniques such as CAQDAS. The results showed that the FKH environmentalcampaign took the form of problem analysis, audience analysis, assigning media,selecting media, developing messages, producing media, implementing programs,monitoring, and evaluating. They use banners, shirts, and facebook groups, usingIndonesian and Banjar languages.